2003
DOI: 10.1046/j.0004-8666.2003.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assessment of bladder volume: Is it valid after delivery?

Abstract: The BladderScan BVI 3000 is not an accurate instrument to assess bladder volume the day after vaginal delivery. Some of the discrepancy might relate to use of the Foley catheter as the reference standard. Further comparison between the BladderScan and a short female catheter or real time ultrasound is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 10 publications
1
16
2
Order By: Relevance
“…In our study, we also found that the acquisition of bladder volume in the same woman is reasonably reproducible (ICC 0.81). This contradicted the low ICC (0.23) obtained by Pallis et al [12]. This difference may be attributed to the difference in methodology; the ICC was analysed in our study using the mean of six BladderScan™ readings per woman whereas Pallis et al used one BladderScan™ reading per woman.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…In our study, we also found that the acquisition of bladder volume in the same woman is reasonably reproducible (ICC 0.81). This contradicted the low ICC (0.23) obtained by Pallis et al [12]. This difference may be attributed to the difference in methodology; the ICC was analysed in our study using the mean of six BladderScan™ readings per woman whereas Pallis et al used one BladderScan™ reading per woman.…”
Section: Discussioncontrasting
confidence: 53%
“…In these studies, the DP technique underestimated [8][9][10] or overestimated [3,5] the catheterised volumes by 17 ml to 52 ml. Further design changes and technology improvement culminated in the BVI3000, which is lighter, has a larger scan plane area of 120°and a quicker scan time of 7 s. To date, there are only a handful of studies that have examined the accuracy of Doppler planimetry in the immediate postpartum period [11][12][13]. In the first few days of the puerperium, the incidence of abnormal voiding parameters is as high as 43% [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between the BVI 2500 and the catheterization measurements was .73 with a mean deviation of 41 ml (95% CI = 26 -55 ml) and the correlation between the BVI 2500+ and catheterization was .94 with a mean deviation of 24 ml (95% CI = 17 -31 ml). Pallis and Wilson (2003) found that urine volumes measured by BVI 3000 were less accurate instruments for assessing bladder volume the day after vaginal delivery than those obtained by catheterization. Huang et al (2001) and Liu et al (2001, August), using the BladderScan BVI 3000 in a study of the measurement of urine volumes, found that catheterization volumes below 100 ml had a mean deviation from ultrasound of 21.13 ml, catheterization volumes between 100 and 200 ml had a mean deviation of 20.89 ml, and volumes above 200 ml had a mean deviation of 31.67 ml.…”
Section: Discussionmentioning
confidence: 88%
“…Distension can be diagnosed with palpation; however, it is too insensitive to diagnose PPUR as the bladder needs to be distended to >300 ml. A bladder scanner or ultrasound can be used to measure bladder distension, although its reliability had been questioned [33][34][35] given the shadow conferred by the immediately postpartum uterus. Catheterization offers the most accurate residual volume measurement in the postpartum period.…”
Section: Postpartum Voiding Dysfunction and Urinary Retentionmentioning
confidence: 99%